Capital Inflows and Balance of Payments Pressures : Tailoring Policy Responses in Emerging Market Economies - Joshi, Bikas; Goretti, Manuela; Ramakrishnan, Uma.; Thomas, Alun. (Washington, D.C. : International Monetary Fund, 2008)
Although capital inflows are generally beneficial to recipient countries, they also pose a challenge for the conduct of economic policy. This paper proposes a conceptual taxonomy to guide the design of policy responses in the face of capital flows. We explore how responses to capital surges should be differentiated based on the source of balance of payments pressures. We also examine whether the policy choices in emerging market countries conform to the taxonomy's predictions and find some correspondence, especially during periods of high global liquidity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet